2015
DOI: 10.1124/jpet.115.225680
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19 Phenoconversion by Routinely Prescribed Proton Pump Inhibitors Omeprazole and Esomeprazole: Clinical Implications for Personalized Medicine

Abstract: The phenotype pantoprazole-13 C breath test (Ptz-BT) was used to evaluate the extent of phenoconversion of CYP2C19 enzyme activity caused by commonly prescribed proton pump inhibitors (PPI) omeprazole and esomprazole. The Ptz-BT was administered to 26 healthy volunteers and 8 stable cardiovascular patients twice at baseline and after 28 days of PPI therapy to evaluate reproducibility of the Ptz-BT and changes in CYP2C19 enzyme activity (phenoconversion) after PPI therapy. The average intrapatient interday vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 28 publications
(47 reference statements)
0
28
1
Order By: Relevance
“…This postulate is consistent with an in vitro study 27 that demonstrated that the magnitude of DCAinduced inactivation effect of GSTZ1 is system specific and differs between different GSTZ1 haplotypes. Based on these findings, we hypothesize that autoinhibition phenoconverts both EGT carriers and noncarriers into slow metabolizers after repeated DCA administration, a phenomenon known as "phenoconversion," reported for many drugs [28][29][30][31] that are predominantly metabolized by phase I enzymes. However, the magnitude of phenoconversion is higher for EGT noncarriers, which converts them into ultraslow metabolizers compared with EGT carriers.…”
Section: Discussionmentioning
confidence: 92%
“…This postulate is consistent with an in vitro study 27 that demonstrated that the magnitude of DCAinduced inactivation effect of GSTZ1 is system specific and differs between different GSTZ1 haplotypes. Based on these findings, we hypothesize that autoinhibition phenoconverts both EGT carriers and noncarriers into slow metabolizers after repeated DCA administration, a phenomenon known as "phenoconversion," reported for many drugs [28][29][30][31] that are predominantly metabolized by phase I enzymes. However, the magnitude of phenoconversion is higher for EGT noncarriers, which converts them into ultraslow metabolizers compared with EGT carriers.…”
Section: Discussionmentioning
confidence: 92%
“…Although mesalamine, AZA, 6‐MP or MTX are not metabolized by CYP2C19, there may be a potential interaction among the drugs. Previous studies have raised concern that proton pump inhibitors (PPIs) may diminish the clinical effectiveness of some medications, possibly by inhibiting the hepatic CYP isoenzymes . In our study, only 5 out of the 79 patients were given concomitant PPIs.…”
Section: Discussionmentioning
confidence: 95%
“…Pharmacological benefits resulting from the chiral (or racemic) switch approach to drug discovery have many precedents, such as esomeprazole overcoming CYP2C19 polymorphism-based differences in peptic ulcer cure rates compared with omeprazole (Klieber et al, 2015) and the antidepressant escitalopram appearing to be more selective in targeting the serotonin reuptake transporter in the absence of the R-enantiomer of citalopram (Sánchez, 2006). Any potential therapeutic benefit of d-MPH over dl-MPH has been largely unknown in the literature, with the exception of overcoming absorption-phase drug interactions with ethanol (Patrick et al, 2013(Patrick et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%